Expression and function of the Scn5a‐encoded voltage‐gated sodium channel NaV1.5 in the rat jejunum. Issue 1 (13th October 2015) - Beyder, A.; Gibbons, S. J.; Mazzone, A.; Strege, P. R.; Saravanaperumal, S. A.; Sha, L.; Higgins, S.; Eisenman, S. T.; Bernard, C. E.; Geurts, A.; Kline, C. F.; Mohler, P. J.; et al.
Abstract: Background: The SCN5A ‐encoded voltage‐gated sodium channel NaV 1.5 is expressed in human jejunum and colon. Mutations in NaV 1.5 are associated with gastrointestinal motility disorders. The rat gastrointestinal tract expresses voltage‐gated sodium channels, but their molecular identity and role in rat gastrointestinal electrophysiology are unknown. Methods: The presence and distribution of Scn5a ‐encoded NaV 1.5 was examined by PCR, Western blotting and immunohistochemistry in rat jejunum. Freshly dissociated smooth muscle cells were examined by whole cell electrophysiology. Zinc finger nuclease was used to target Scn5a in rats. Lentiviral‐mediated transduction with shRNA was used to target Scn5a in rat jejunum smooth muscle organotypic cultures. Organotypic cultures were examined by sharp electrode electrophysiology and RT‐PCR. Key Results: We found NaV 1.5 in rat jejunum and colon smooth muscle by Western blot. Immunohistochemistry using two other antibodies of different portions of NaV 1.5 revealed the presence of the ion channel in rat jejunum. Whole cell voltage‐clamp in dissociated smooth muscle cells from rat jejunum showed fast activating and inactivating voltage‐dependent inward current that was eliminated by Na + replacement by NMDG + . Constitutive rat Scn5a knockout resulted in death in utero . NaV 1.5 shRNA delivered by lentivirus into rat jejunum smooth muscle organotypic culture resulted in 57% loss of Scn5a mRNA and several significant changes in slow waves, namely 40% decrease in peak amplitude, 30% decrease in half‐width, and 7 mV hyperpolarization of the membrane potential at peak amplitude. Conclusions & Inferences: Scn5a ‐encoded NaV 1.5 is expressed in rat gastrointestinal smooth muscle and it contributes to smooth muscle electrophysiology. Abstract : The voltage‐gated Na + channel NaV 1.5, encoded by the gene SCN5A, is expressed in human GI tract and is associated with functional GI disorders. Here we found that Scn5a is also expressed and functional in rat jejunal smooth muscle; knockdown of Scn5a expression with shRNA reduced the amplitude and half‐widths of jejunal smooth muscle electrical slow waves. This study demonstrates a role for the voltage‐gated mechanosensitive ion channel NaV 1.5 in normal gastrointestinal motility in the rat and establishes the rat as an important model for study of the Scn5a ‐encoded NaV 1.5 in gastrointestinal physiology and pathophysiology.